ANALISIS ‬BIBLIOMETRIK TREND PENELITIAN JURNAL IQRA (JURNAL PERPUSTAKAAN DAN INFORMASI) PERIODE 2017-2021 MENGGUNAKAN ‬VOS VIEWER‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ - Fauzi, Ahmad; Purwaningtyas, Franindya (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study aims to determine the map of the development of research trends in the IQRA Journal for the 2017-2021 period. This study formulates the problem of how the development of article publication trends and literature patterns in IQRA articles (Library and Information Journal) published in 2017-2021. This study used a descriptive research method with a quantitative approach using bibliometric analysis techniques. Mapping is done with co-word based mapping. The research sample is 89 IQRA articles for 2017-2021. In this study, two supporting applications in bibliometrics were used, namely Mendeley and VOSViewer. The results of the study show that the visualization of the results of research data processing using the 2017-2021 IQRA journal metadata is grouped into 4 clusters. The results of the VOSViewer analysis seen from the overlay visualization that the research topic in the journal IQRA 2017-2021 which has been carried out for a long time is about librarians and the latest research on services. The results of the density visualization mean that the keyword groups in the 2017-2021 IQRA journal have a relationship with each other, in which the most frequently researched topic is the library. Judging from its development, the most published articles published by the IQRA Journal were in 2019 and the lowest was in 2021.